Functional Classification Systems for Children with Cerebral Palsy:An ICF-Based Approach - azade riyahi; Mehdi rassafiani; Afsoon Hassani Mehraban; Malahat Akbarfahimi (Shiraz University of Medical Sciences, 2024)
Background: Cerebral palsy is one of the most prevalent physical disabilities in childhood. Children afflicted with this condition face a myriad of challenges and potential disabilities, which complicate treatment efforts. Integrating scales with other diagnostic instruments is increasingly crucial for accurately assessing these children and devising effective treatment strategies. This study primarily aims to review functional classification systems based on the International Classification of Functioning, Disability, and Health (ICF) for children with cerebral palsy and explore the relationships among these systems.methods: This study was designed to review the ICF-based functional classification systems. A comprehensive search was conducted across multiple databases, including Google Scholar, PubMed, ERIC, OVID, ProQuest, Scopus, Web of Knowledge, and OTseeker. Search terms related to cerebral palsy and various aspects of body function, activity, and participation were utilized. The search was conducted until September 2022 to gather relevant literature for analysis.Results: The analysis of the reviewed articles revealed the existence of five valid and reliable classification systems. In most studies, the correlation among these systems was moderate. Owing to their simplicity and comprehensiveness, these classification systems have significantly impacted the depiction of the functional status of children with cerebral palsy and the quality of their care. However, additional classification systems remain needed to address other overlooked functions and complete the overall description.Conclusion: The outcomes of this review indicated the development of classification systems for certain functions in children with cerebral palsy. In conjunction with the classifications above, creating additional new systems for overlooked functions could offer a comprehensive and integrated understanding of children with cerebral palsy's crucial functional capacities and performances.